IMPLEMENTASI PUTUSAN DISPUTE SETTLEMENT BODY (DSB) WORLD TRADE ORGANIZATION (WTO) OLEH AUSTRALIA TERHADAP SENGKETA PRODUK KERTAS FOTOKOPI A4 ASAL INDONESIA - Dilla, Arifa Rahma; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The dispute concerning dumping allegations made by Australia against A4 copy paper products originating from Indonesia arose when the Australian Anti- Dumping Commission (ADC) imposed high anti-dumping duties on three Indonesian paper companies. Consequently, Indonesia filed a complaint against Australia through the World Trade Organization (WTO) dispute settlement mechanism. This study employs a qualitative approach with a descriptive method. Data were collected through literature reviews, official documents from the World Trade Organization (WTO), as well as government publications from both countries. The research is framed using the theoretical perspective of liberalism, theories of international dispute resolution, and the nation-state level of analysis. The findings indicate that Australia has implemented the decision of the WTO Dispute Settlement Body (DSB) by revoking anti-dumping duties on two out of three Indonesian paper exporters in 2020. This measure was taken after a lengthy litigation process in which the WTO panel ruled that Australia had violated provisions under the Anti-Dumping Agreement. Keywords: World Trade Organization, Dispute Settlement Body, Anti-Dumping Commission, Anti-Dumping Duties, Anti-Dumping Agreement.